Retrospective Evaluation of the Use and Complications of Small-Bore Wire-Guided Thoracostomy Tubes in Dogs and Cats: 156 Cases (2007–2019) - Boullhesen Williams, Tomas; Fletcher, Daniel; Fusco, Jacqueline; Bichoupan, Allison; Weikert, Lisa; Barenas, Mario; Menard, Julie (Frontiers in Veterinary Science, 2022)
Background: Small-bore wire-guided thoracostomy tubes (SBWGTT) are commonly used in small animals for management of pleural space disease. We aimed to evaluate the indications, placement locations, types of complications, and complication rate of small-bore wire-guided thoracostomy tubes placements in dogs and cats in a university setting. Methods: Electronic medical records of patients that underwent SBWGTT placement were reviewed. Signalment, disease, outcome, indication for thoracostomy tube, placement location, number of attempts, diagnostic imaging, number, and type (insertional, technical, and infectious) of complications were recorded. Logistic regression analysis was performed to determine risk factors for complications. Results: 156 cases were identified between 2007-2019. Traumatic pneumothorax (33%), pyothorax (25%), and spontaneous pneumothorax (16%) were the most common indications for placement of a SBWGTT. Complications developed in 50 cases (32%). Technical and insertional complications accounted for 21.7% and 14.1 % of all cases. Infectious complications were rare with 3.1% of all cases. Pneumothorax (19%), soft tissue swelling at insertion site (14%) and kinking of the chest tube (13%) were most common. Accidental lung perforation was reported in 5/50 complications (7%). Multiple chest tubes placement attempts were associated with complications (OR=6.01 CI: 2.13 to 16.93 p = 0.0007). Conclusions: Complications of SBWGTT placement occurred in 1/3 of cases. Serious complications such as accidental lung perforation was reported in 2 cases. Complications were associated with number of attempts.